The Relationship Between Convergent IGH Signatures and Severity of COVID-19 Patients by Next-Generation Sequencing of B-Cell Repertoire - Cai, Hongliu; Hu, Juan; Huang, Lingtong; Gao, Chunhua; Xu, Mi; Gao, Yuzhi; Sun, Tao; Fang, Xueling (Frontiers in Microbiology, 2022)
Object To reveal convergent IGH signatures and the association with severity of coronavirus disease 2019 (COVID-19) patients. Method A total of 25 COVID-19 inpatients were classified into three clinical conditions: mild, severe, and critical. We analyzed convergent IGH signatures by ImmuHub® B-cell receptor (BCR) profiling system. Results IGH singleton frequency in patients is significantly lower than that of healthy donors (HDs). The clonality index of IGH in patients is significantly higher than that in HDs. Nevertheless, no significant difference was observed among the three groups. The difference in IGH clonality (top five clones) between post- and pretreatment was significant in the improvement and deterioration groups. Three common public motifs were shared by all COVID-19 patients: ARDYGG, RWYFDY, and YYYYGMDV. Conclusion B cells could recognize severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and produce clonal expansion. Patients who had better outcomes after treatment had higher IGH clonality. Three common public motifs—ARDYGG, RWYFDY, and YYYYGMDV—might be used for vaccine development (ChiCTR2000029626).